The Perception of Filipino Consumers in District II, Caloocan City on Factors Affecting Buying Decision Towards Non-Life Insurance: A Basis for Marketing Strategy - Anada, Maria Jella I.; Antonio, Carl Jason R.; Arsenal, John Carl S.; Fayen, Veronica Grade D.; Lopez, Joyce Krisneza P. and Tambio, Cyrril Mae C., 2014 4 0 16; 5
ABSTRACT: This study aims to know the perception of Filipino consumers on factors affecting their buying decision towards non-life insurance specifically in District 2, Caloocan City. The researcher come up with this topic as they got interested regarding the concept insurance and one of the researchers experienced to train in one of the non-life insurance company in the Philippines. The major purpose of the researchers is to study factors that affect the buying decision of Filipino Consumers in District 2, Caloocan City. Specifically, the researcher attempted to answer the following questions: What are the factors that affecting non-life insurance among the Filipinos considering their demographic profile. Are the Filipino Consumers in District 2, Caloocan City who are aware of the non-life insurance as to product are policyholder? What are the perception of the Filipino consumers in District 2, Caloocan City towards Non-Life Insurance as to: cost of insurance, reasons to avail and their financial capacity or capability. And lastly, is there a significant difference between those who are policyholder and not policyholder in terms of the factors that affect their buying decisions? In this study, the hypothesis to be tested is There is no significant difference between the perception of policyholders and non-policyholders of Non-Life Insurance in District 2, Caloocan City in terms of the factors that affect their buying decisions. To answer these questions, the researchers embraced the descriptive method of research under the normative survey technique, a fact study adequate and accurate interpretation. (Ladisla, 2009). Under this method is the survey method research. The researchers prepared an unstructured questionnaire in a clear, readable and understandable way that can be answered by the respondents. The respondents of this study are chosen from random individuals in District 2 Caloocan City. Based on the data gathered by the researchers the following conclusions were made: Majority of the Filipino consumers in Caloocan who are a policyholder are male. Ages 36-43 types of Filipino consumers mostly consume non-life insurance. As to the average monthly income, Filipino consumers who earn P30,000-P40,000 monthly insured their properties to non-life insurance. While Filipino consumers who earn P11,000-P20,000 monthly, they tend to refuse non-life insurance from the possibility that they have insufficient income to acquire such products. Majority of the Filipino consumers who are policyholder are college graduate. As to properties owned, the factor is the principle of insurable interest. Filipino consumers will have legal interest only to their properties and therefore will only insure property they owned. Majority of the respondents are not a policyholder. Among the policyholder, majority of the respondents are not a policyholder. Among the policyholder, majority of them availed Ca Insurance.
Thesis: (BSBA major in Finance and Treasury Management) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2